Metal-free production of natural blue colorants through anthocyanin–protein interactions - Wenxin Wang; Peiqing Yang; Fuqing Gao; Yongtao Wang; Zhenzhen Xu; Xiaojun Liao (Journal of Advanced Research)
Introduction: The scarcity of naturally available sources for blue colorants has driven reliance on synthetic alternatives. Nevertheless, growing health concerns have prompted the development of naturally derived blue colorants, which remains challenging with limited success thus far. Anthocyanins (ACNs) are known for providing blue colors in plants, and metal complexation with acylated ACNs remains the primary strategy to generate stable blue hues. However, this approach can be costly and raise concerns regarding potential metal consumption risks. Objectives: Our study aims to introduce a metal-free approach to achieve blue coloration in commonly distributed non-acylated 3-glucoside ACNs by exploring their interactions with proteins and unveiling the underlying mechanisms. Methods: Using human serum albumin (HSA) as a model protein, we investigated the structural influences of ACNs on their blue color generation using visible absorption spectroscopy, fluorescence quenching, and molecular simulations. Additionally, we examined the bluing effects of six proteins derived from milk and egg and identified the remarkable roles of bovine serum albumin (BSA) and lysozyme (LYS). Results: Our findings highlighted the importance of two or more hydroxyl or methoxyl substituents in the B-ring of ACNs for generating blue colors. Cyanidin-, delphinidin- and petunidin-3-glucoside, featuring two neighboring hydroxyl groups in the B-ring, exhibited blue coloration when interacting with HSA or LYS, driven primarily by favorable enthalpy changes. In contrast, malvidin-3-glucoside, with two methoxyl substituents, achieved blue coloration through interactions with HSA or BSA, where entropy change played significant roles. Conclusion: Our work, for the first time, demonstrates the remarkable capability of widely distributed 3-glucoside ACNs to generate diverse blue shades through interactions with certain proteins. This offers a promising and straightforward strategy for the production of ACN-based blue colorants, stimulating further research in this field.